Primary Malignant Melanoma of the Vagina: A Retrospective Clinicopathologic Study of 44 Cases. Issue 1 (1st January 2014) - Xia, Lingfang; Han, Duo; Yang, Wentao; Li, Jin; Chuang, Linus; Wu, Xiaohua
Abstract : Objective: This study aimed to identify prognostic factors of survival and improve treatment strategies in women diagnosed with primary malignant melanoma of the vagina. Methods: Between December 2002 and August 2011, 44 patients with lesions confined to the vagina and diagnosed with melanoma at Fudan University Shanghai Cancer Center were evaluated retrospectively. Prognostic factors were analyzed by Kaplan-Meier method. Results: With a median follow-up time of 18.9 months (range, 6.0–94.3 months), 30 (68.2%) patients developed recurrences, whereas 21 (47.7%) died of disease. Median progression-free survival (PFS) was 14.4 months and median overall survival (OS) was 39.5 months. Depth of invasion (DOI) was significantly associated with OS ( P = 0.023), and there was an obvious tendency toward improved OS with a negative lymph node status ( P = 0.063). The DOI was significantly associated with lymph node status ( P = 0.047). The extent of surgery (wide local excision vs radical excision) was not associated with differences in PFS or OS ( P = 0.573 and P = 0.842, respectively). Longer PFS was observed in patients who received adjuvant chemotherapy and radiotherapy ( P = 0.038). Conclusions: The prognosis of primary vaginal melanoma is dependent on the DOI and lymph node status in our study. Surgical resection of disease, especially wide local excision, should be considered as the optimal treatment when complete removal of tumor with a negative margin is possible. Adjuvant therapy may be associated with a longer PFS.